Design is storytelling - Lupton, Ellen (New York, NY : Cooper Hewitt, Smithsonian Design Museum, 2017)
Good design, like good storytelling, brings ideas to life. The latest book from award-winning writer Ellen Lupton is a playbook for creative thinking, showing designers how to use storytelling techniques to create satisfying graphics, products, services and experiences. Whether crafting a digital app or a data-rich publication, designers invite people to enter a scene and explore what's there. An intriguing logo, page layout or retail space uses line, shape and form to lead users on dynamic journeys. 'Design Is Storytelling' explores the psychology of visual perception from a narrative point of view. Presenting dozens of tools and concepts in a lively, visual manner, this book will help any designer amplify the narrative power of their work. Use this book to stir emotions, build empathy, articulate values and convey action; to construct narrative arcs and create paths through space; integrate form and language; evaluate a project's storytelling power; and to write and deliver strong narratives. --! From back cover.
Overture -- Foreword -- Acknowledgments -- Inciting incidents -- Act 1. Action -- Narrative arc -- Hero's journey -- Storyboard -- Rule of threes -- Scenario planning -- Design fiction -- Act 2. Emotion -- Experience economy -- Emotional journey -- Co-creation -- Persona -- Product profile -- Emoji -- Color and emotion -- Act 3. Sensation -- The gaze -- Gestalt principles -- Affordance -- Behavioral economics -- Multisensory design -- Aftermath -- Clinic: Improve your writing -- Classroom: Project generator -- Takeaway: Storytelling checklist -- Index.
Includes index.
"This book explores connections between storytelling and design. It examines the psychology of visual communication from a narrative point of view."--Publisher's description.
Keywords: Design -- Human factors; Design -- Psychological aspects; Storytelling in art; Visual communication -- Psychological aspects; Creative thinking